Integrated adsorption and photocatalytic degradation of volatile organic compounds (VOCs) using carbon-based nanocomposites: A critical review - Zou, Weixin; Gao, Bin; Ok, Yong Sik; Dong, Lin (Chemosphere (Oxford), 2019)
Volatile organic compounds (VOCs) are harmful for human and surrounding ecosystem, and a great number of VOC abatement technologies have been developed during the past few decades. However, the single method has some problems such as high energy consumption, unfriendly environment, and low removal efficiency. Recently, the integration of adsorption and photocatalytic degradation of VOCs is considered as a promising one. Carbon material, with large surface area, high adsorption capacity, and fast electron transfer ability, is widely used in integrated adsorptive-photocatalytic removal of VOCs. It is thus crucial to digest and summarize recent research advances in carbon-based nanocomposites as the adsorbent-photocatalyst for VOC removal. To satisfy this need, this work provides a critical review of the related literature with focuses on: (1) the advantages and disadvantages of various carbon-based nanocomposites for the applications of VOC adsorption and photocatalytic degradation; (2) models and mechanisms of adsorptive-photocatalytic removal of VOCs according to the material properties; and (3) major factors controlling adsorption-photocatalysis processes of VOCs. The review is aimed to establish the “structure-property-application” relationships for the development of innovative carbon-supported nanocomposites and to promote future research on the integrated adsorptive and photocatalytic removal of VOCs. •The advantages and disadvantages of carbon-supported hybrids were discussed.•Adsorption and photocatalytic models of VOC removal were reviewed.•The reaction processes and intermediates were proposed.•Major factors controlling adsorptive-photocatalytic reactions were discussed.